Manajemen Pengetahuan Dan Modal Sosial Dalam Pengembangan Sumber Daya Manusia - Ahmad Muhammad Diponegoro (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2000)
The purpose of study is to compare two current western theories of knowledge management that was written by Senge and Nonaka and social capital management with Islam. It was believed. That those theories were very important to overcome the crisis that hit some countries. The result was Islam has theories that equally well compare to western, doesn’t out of date and still applicable in modern society. Kata Kunci : managemen, pengetahuan , modal sosial dan pengembangan sumber daya manusia